Dual Role Burden among Female Agricultural Laborers in Rural Indonesia - Fasatin Nafisah; Martoyo Martoyo; Muhammad Faisol (Academia Open, 2026)
General Background: Women’s participation in public economic activities has increased alongside evolving gender roles in Indonesian society, yet normative legal frameworks emphasize balanced rights and obligations within households. Specific Background: Female agricultural laborers in Ramban Kulon Village simultaneously engage in income-generating activities and domestic responsibilities, reflecting a complex interaction between socio-legal norms and rural realities. Knowledge Gap: Despite formal recognition of gender equality in Islamic family law and national legislation, discrepancies persist in the practical division of household roles, particularly in agrarian communities. Aims: This study aims to analyze the forms of problems experienced by female agricultural laborers and identify the social and economic factors contributing to these challenges. Results: Findings reveal excessive double workloads, limited recovery time, and unequal domestic role distribution, driven by patriarchal norms and unstable household income. Women’s economic participation does not alter domestic responsibilities, resulting in sustained role conflict and structural burden. Novelty: This study highlights the interaction between socio-cultural structures and economic necessity in shaping persistent dual role conditions among rural women within a socio-legal framework. Implications: The findings underscore the need for gender-responsive policies and community-based interventions addressing structural inequality and promoting equitable role distribution in rural households. Highlights: Simultaneous domestic and agricultural responsibilities create continuous physical and emotional strain. Patriarchal cultural norms maintain unequal household task allocation despite income contribution. Seasonal and unstable earnings drive women’s labor participation without shifting family role structures. Keywords: Women's Dual Roles, Farm Laborers, Family Problems